Dynamics of morbidity of mental disorders of neurotic origin in the Ternopil region in the context of global warmin - S. N. Vadzyuk; T. V. Kharkovska (Kazimierz Wielki University, 2021)
Relevance: Over the last century, the modern climate is characterized by an average annual increase in global air temperature. According to existing scientific data, heat waves are often accompanied by mental, behavioral disorders that are combined with mood swings and increased anxiety. That is why the analysis of the incidence of mental disorders of the neurotic spectrum in the Ternopil region in the context of global warming is relevant. Materials and methods: To analyze the incidence of mental disorders of the neurotic spectrum, the archival data of the Ternopil Regional Clinical Psychoneurological Hospital for 10 years, from 2010 to 2019 were analyzed. The average annual air temperatures were determined according to the archival data of hydrometeorological observations by the meteorological station of the city of Ternopil during 2010-2019. The growth rate of these indicators was estimated by the time series method. Pearson's correlation coefficient was used to measure the degree of linear dependence between two variables, namely the rate of hospitalization growth and the average annual temperature in the region. Tables and graphs are built using Microsoft Excel and Microsoft Word. Results: The primary analysis of the incidence of mental disorders of the neurotic spectrum in Ternopil region showed that the percentage growth rate for the year ranged from -19.55% to + 20.62% and it was difficult to determine the direction of this phenomenon. In this regard, we carried out the alignment of the series by increasing the period and determining the arithmetic mean of the data for three years, respectively, we obtained data showing that for 10 years the prevalence of mental disorders of the neurotic spectrum in Ternopil region increased, the growth rate ranged from + 1.66% to + 6.32%. Conclusions: Analyzing the obtained results, we found that in the conditions of global warming in Ternopil region there is a dynamics of growth in the incidence of mental disorders of neurotic origin. Also, by calculating the correlation coefficient, a direct correlation between the increase in the average annual temperature and the increase in morbidity rates was proved. The data obtained should be taken into account in the development of protocols for the prevention and treatment of mental illness associated with the effects of climate change, and will also be used in the educational process at the Departments of Physiology, Pathological Physiology and Psychiatry.